Origen de la competencia del poder civil sobre las iglesias en las doctrinas protestantes: estudio histórico e interés actual - Roca, María J. (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
This study tries to explain the episcopal, territorial and collegiate theories. These are the successive theorist doctrines worked out by Protestant authors of public law to justify that ecclesiastical matters were within the discretion of civil power (territorial lords). Whereas episcopal theory tries to justify that these episcopal powers are granted to territorial lords until Reformed churches reunited Roman Catholic Church, the territorial theory argue that is the territory which entitle the Protestant princes to exercise their jurisdiction over the churches. On an certain territory, civil authority exercises an absolute power which includes ecclesiastical affairs. The collegiate theory attempts to limit these absolute power. Collegialism maintains that churches, as every college, have a particular self-government based on their collegiate rights. This study makes clear that these doctrines bear a close relation to the historically prevailing state theory.